IMPLEMENTASI MEDIA TERHADAP RESPON SISWA DALAM PENGEMBANGAN KARTU BERGAMBAR KREATIF PADA TOPIK TRANSFORMASI ENERGI DI SEKITAR KITA PADA SISWA KELAS 4 DI SDN DUKUH PUNDONG 2 JOMBANG - Chantika Bahtra Dewi; Muhammad Nuruddin (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The purpose of this research is to find out how media is implemented on student responses in developing creative picture card media at SDN Dukuh Pundong 2 Jombang. The method used in the research is the RnD method which is usually used in development methods, but this research focuses on the Barg and Gall theory which has been modified by Sugiyono (2010). The subjects used in this research were fourth grade students at SDN Dukuh Pundong 2 Jombang, where there were 20 students in one class. Then the data collection instruments used in this research were observation, interviews, documentation and questionnaire sheets. This research also found several results where the learning process carried out at SDN Dukuh Pundong 2 Jombang still used the lecture method and the media used was still very minimal. Meanwhile, the obstacles that occur at this school during the learning process are that students are still not directly required to be more active, students do direct practice with media, there is no media used that is related to P5 learning and students at SDN Dukuh Pundong 2 Jombang are not enthusiastic when in class. especially in science learning regarding the topic of energy transformation around us.